Step-by-Step, an E-Mental Health Intervention for Depression: A Mixed Methods Pilot Study From Lebanon - Harper Shehadeh, Melissa Joanne; Abi Ramia, Jinane; Cuijpers, Pim; El Chammay, Rabih; Heim, Eva; Kheir, Wissam; Saeed, Khalid; van Ommeren, Mark; van’t Hof, Edith; Watts, Sarah; Wenger, Andreas; Zoghbi, Edwina; et al. (Frontiers in Psychiatry, 2020)
Background: E-mental health is an established mode of delivering treatment for common mental disorders in many high income countries. However, evidence of its effectiveness in lower income countries is lacking. This mixed methods study presents preliminary data on the feasibility of a minimally guided e-mental health intervention in Lebanon. The aim was to pilot test Step-by-Step, a WHO guided e-mental health intervention, prior to future controlled testing. Methods: Participants were recruited using social media and advertisements in primary care clinics. Participants completed baseline and post-intervention questionnaires on depression symptoms (primary outcome, PHQ-8), anxiety symptoms, wellbeing, disability and self-perceived problem severity and a client satisfaction questionnaire. In addition, seven completers, four drop-outs, eleven study staff and four clinic managers were interviewed with responses thematically analyzed. Website analytics were used to understand participant behavior when using the website. Results: A total of 129 participants signed up via the Step-by-Step website. 74 participants started session 1 after completing pre-test questionnaires and 26 completed both baseline and post intervention data. Among those who completed post-assessments, depression symptoms improved (PHQ-8 scores (t=5.62, p<0.001 2 tailed, df=25). Wilcoxon signed ranks tests showed a significant difference between baseline and post-Step-by-Step scores on all secondary outcome measures. Client satisfaction data was positive. Interview responses suggested that the intervention could be made more appropriate for younger, single people, more motivating and easier to use. Those who utilised the support element of the intervention were happy with their relationship with the non-specialist support person (e-helper), though some participants would have preferred specialist support. E-helpers would have liked more training on complex cases. Website analytics showed that many users dropped out before intervention start, and that some re-entered screening data having been excluded from the study. Conclusion: Step-by-Step skills and techniques, model of service integration and non-specialist support element are acceptable. Though the sample was small and non-controlled and drop-out was high, results suggest that it may be effective in reducing depression and anxiety symptoms and increasing wellbeing. Lessons learned will inform content revision, the development of an app version of Step-by-Step and the research methodology of upcoming effectiveness studies.